How does cold water impact on human physiology? Recent research discoveries - Wiktor Wróblewski; Paweł Zalewski; Dariusz Gruca; Adam Raabe; Marcin Wais (Kazimierz Wielki University, 2024)
We analysed the newest research conducted from 2019 to 2023. The study was searched in the online databases, especially in PubMed. Results: The newest studies are not consistent with the impact of cold water after training sessions on muscle performance and regeneration.  There are no coherent results of the impact on biochemical immunological and hormonal parameters. Research showed that cold water has a good impact on heart recovery after strain. CWI can remove the positive effect of hypotension after exercise. Studies show no impact of CWI on PCG1-α in muscles with a depletion level of glycogen but there is a need for consideration that CWI can benefit when muscle glycogen is at a higher level. It seems that CWI has a more efficient effect of vasoconstriction than PBC.  There are suggestions that CWI can increase insulin sensitivity and better glucose tolerance after fasting sessions. There are suggestions that 18-degree water can cause an acute decrease in cognitive function. Immersion in cold water which is defined in that study as 20-25℃ can benefit RLS among pregnant women.  Conclusions: On the grounds of the newest studies, it is hard to come to a clear conclusion about the impact of cold water on the human body. There is a need for further studies with large and diverse groups of contestants. Results from studies analysed in that article can help design the next studies. At that moment there was no undisputed evidence of the beneficial impact of cold water on human physiology.